ANALISIS KINERJA REKSADANA KONVENSIONAL DAN REKSADANA SYARIAH UNTUK KEPUTUSAN INVESTASI INVESTOR - Riri Indriani; Triyani Budyastuti (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2021)
The purpose of his research are to know, describe and analyze the performance of comparisoon between conventional mutual fund and sharia mutual fund for investor’s investment decision based on Sharpe, Treynor, Jensen and growth of AUM (Asset Under Management). The object for this research is conventional share mutual fund, sharia share mutual fund, conventional fixed income mutual funds and sharia fixed income mutual funds. This research uses Nav data (Net Asset Value) from 2015 until 2017 with sample number 52 mutual fund which have been selected by Purposive Sampling method. This research uses the data analysis is statistical analysis in the form of average difference test using independent sample t-test method. The result of this research is no difference in analysis conventional mutual fund and Shariah mutual fund performance  using Sharpe method and AUM (Asset Under Management) and have differences in analysis conventional mutual fund and Shariah mutual fund  using Treynor and Jensen method.